Response of the EU Member States to Climate Change in the Context of EU Policy and Strategy - Wysokińska, Zofia (Comparative Economic Research. Central and Eastern Europe, 2014)
The aim of this paper is to present selected results achieved by the Member States of the EU in the context of the recent global and European strategies oriented toward enhancement of the role of renewable energy sources and on mitigation of negative climate changes in the Earth. Special attention has been paid to those countries that have approached or already reached, in the year 2012, a share of renewable energy indicators at a percentage level higher than the required 20%.